Engineering cathode and anode for rechargeable aluminum-ion aqueous battery - Sonal, Kumar (Nanyang Technological University, 2021)
Rechargeable aluminum-ion aqueous battery (AIAB) is extremely attractive from the prospects of developing environmentally and economically sustainable battery energy storage systems. The usage of water as an electrolyte solvent in AIAB makes it inherently non-flammable and presents opportunities for open-air fabrication, making it safer and cheaper. At the same time, AIAB presents opportunities of getting rid of lithium while harnessing aluminium’s (Al’s) high volumetric capacity (~8000 mAh cm-3) and low cost because of the high abundance in the earth’s crust. Hence, AIAB is a strong contender for futuristic energy storage applications, challenging established commercial battery chemistries. However, the AIAB battery research is nascent and presents challenges on both the cathode and anode front, often raising questions about the feasibility and practicality of such viable battery chemistry. This thesis is an effort towards to studying Al-ion batteries and answering this feasibility question by testing novel cathodes and anodes in water-based electrolyte.